Reassessing The Limits of Humanity in Executing Humanitarian Intervention within the RtoP Framework - Sasmini (Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2025)
Humanitarian Intervention (HI) is the third pillar of the Responsibility to Protect (RtoP) framework, which frequently invokes the concept of humanity as the fundamental source of legitimacy. However, the absence of clear criteria defining the limit of humanity has led to a double standard in the implementation. Therefore, this study aims to examine two main legal issues, namely the broader legal implications of the principle of humanity in the international legal system and the standard threshold to legitimize the intervention within the RtoP framework. A doctrinal legal method was used with regulatory, conceptual, and case approaches. In addition, interpretative methods were used for legal argumentation. The results showed that the concept of humanity has historically played a crucial role in shaping international law. The evolution of international humanitarian law (IHL) and international human rights law, particularly within the context of international criminal law, is closely related to the concept of humanity. According to this concept, intervention may be justified to prevent and stop humanitarian crises within a specific state to protect the victims. However, only actions that exceed the limits of humanity, including extraordinary acts of cruelty and crimes under universal jurisdiction, can serve as the basis for HI legitimacy. Moreover, the threshold for invoking HI must also include a determination that the state is unwilling or unable to prevent or stop the ongoing atrocities.